Pemberdayaan Penyandang Disabilitas Pada Program PermataBRAVE Corporate Social Responsibility (CSR) PT Bank Permata Tbk - Wahyudi, Ayuananda; Nurwulan, Riany Laila (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
The right to accessibility in obtaining employment is one of the major challenges faced by persons with disabilities. Many of them are unable to secure jobs due to low educational backgrounds and a lack of skills. Through empowerment initiatives under Corporate Social Responsibility (CSR) programs in companies, persons with disabilities can fulfill their daily needs by becoming employees in these companies. One such company with a CSR program aimed at people with disabilities is Permata Bank. Based on this background, the researcher conducted a study on Corporate Social Responsibility (CSR) with the theme: